Therapeutic efficacy of silymarin and naringenin in reducing arsenic-induced hepatic damage in young rats - Jain, Anshu; Yadav, Abhishek; Bozhkov, A.I.; Padalko, V.I.; Flora, S.J.S. (Ecotoxicology and environmental safety, 2011)
We investigated the effects of silymarin and naringenin in counteracting arsenic-induced hepatic oxidative stress post exposure. Male wistar rats were chronically exposed to sodium arsenite for eight months followed by oral treatment with silymarin and naringenin (50 mg/kg each) for 15 consecutive days to evaluate hepatic damage and antioxidant potential. Our results demonstrate a significant decrease in hepatic GSH levels, SOD and catalase activities and an increase in GST and TBARS levels after arsenic administration. Silymarin or naringenin administration increased GSH levels and was beneficial in the recovery of altered SOD and catalase activity besides significantly reducing blood and tissue arsenic concentration. Our results point to the antioxidant potential of these flavonoids, which might be of benefit in the clinical recovery of subject exposed to arsenic. These flavonoids can be incorporated into the diet or co-supplemented during chelation treatment, and thus may afford a protective effect against arsenite-induced cytotoxicity.